MODELLING AND IMAGING THE MOHO TRANSITION: THE CASE OF THE SOUTHERN URALS - Carbonell R.; Gallart J.; Pérez-Estaún A. (My University, 2002)
Synthetic seismic modelling is used to test different possible structures and forming processes of the lower crust and Moho. One and two dimensional synthetic seismic modelling of the Moho reflection is carried out to constrain the internal structure of a crust–mantle transition. A reflectivity algorithm was used to calculate the synthetic seismograms for models of the crust–mantle transition consisting of gradient zones and layered sequences. The synthetic seismograms for models consisting of laterally variable velocity structure were calculated by an explicit finite difference wave equation algorithm. The laterally heterogeneous transition models can be achieved by assuming a Moho with different degrees of variable topography or laterally discontinuous layering. The effects of a low velocity surface cover on the seismic signature of deep signals is also analysed. The seismic modelling coupled with stacked images of wide-angle seismic reflection data constrain the case history of the Moho transition beneath the southern Urals. A smooth gradational crust–mantle transition (gradient velocity–depth function) does not predict the seismic features observed in the shot records. The coda of the PmP and the amplitude behaviour of this phase with offset are modelled with a 6 km thick transition zone which consists of approximately 600 m thick, laterally variable layers with a bimodal velocity distribution. The horizontal component stacks of the wide-angle data feature arcuate events suggesting boudin like structures or a boundary with topographic relief. High amplitude sub-Moho reflections support that the structural complexity of the crust–mantle transition can be followed to the upper mantle suggesting eastward dipping structures indicating, either, remnants of an old subduction zone, trapped crustal material within the mantle, or active crust–mantle interactions.